2009
DOI: 10.1002/adma.200801256
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Function of a Complex Three‐Dimensional Suture Joining the Bony Elements in the Shell of the Red‐Eared Slider Turtle

Abstract: The shell of turtles is a shield which needs to be stiff at high loads but should provide sufficient flexibility for respiration and locomotion at smaller loads. We show that this seemingly contradictory requirement is met by a self‐locking material, whereby stiff bony elements are connected by a much softer suture with a complex three‐dimensional shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 27 publications
1
99
1
Order By: Relevance
“…Such a design renders materials with a high tolerance with respect to local failures, and can be applied to surface protection with brittle material. [16,17] Fratzl et al [18] also found such an interlocking structure in the suture of turtle shell. The interlocking mosaic structure in CU shells probably plays a similar role.…”
mentioning
confidence: 88%
“…Such a design renders materials with a high tolerance with respect to local failures, and can be applied to surface protection with brittle material. [16,17] Fratzl et al [18] also found such an interlocking structure in the suture of turtle shell. The interlocking mosaic structure in CU shells probably plays a similar role.…”
mentioning
confidence: 88%
“…7). Sutures have been found to influence patterns of stress and strain by resisting or allowing deformations depending on load orientation and/or magnitude (Rafferty et al, 2003;Markey et al, 2006;Krauss et al, 2009) but can also act as bone deposition sites in mammals (Opperman, 2000;Sun et al, 2004) and so may provide free surfaces for growth and bone deposition in billfish rostra. All of these factors may decrease the likelihood of failure at this region, preventing the compromise of vital organs such as the nares, and also preventing damage to a region of higher vascularization and growth.…”
Section: Discussionmentioning
confidence: 99%
“…9(c) that there are no Sharpey's fibers spanning between the mineralized teeth. Sharpey's fibers are frequently observed bridging hard plates, such as in the armadillo osteoderm [6], turtle carapace [42] and cranial plates [44].…”
Section: Mechanical Characterizationmentioning
confidence: 99%